INFLUENCE OF ULTRAFINE FILLERS ON THE PROPERTIES OF LOW-MOLECULAR LIQUIDS AND COMPOSITIONS BASED ON EPOXY OLIGOMERS - A. A. Pykhtin; P. V. Surikov; L. B. Kandyrin; V. N. Kuleznev (Тонкие химические технологии)
In this work the preparation of polymeric composite materials (PCM) based on an ED-20 grade epoxy resin with the use of carbon nanotubes (MWNT), technical carbon (N220) and aerosol (A380) and the influence of midget additives of these fillers on the complex of optical, rheological and physicomechanical properties were investigated.